Actinomycotic lid abscess: a rare presentation - Karandikar, Sumita; Karandikar, Sangram; Shaikh, Tanveer Parvez; Ansari, Sharique (International Journal of Research in Medical Sciences, 2017)
Actinomycosis is a gram positive filamentous branching anaerobic bacilli that Is difficult to Isolate and Identify. We present this case of a 15 year old patient who developed repeated infection over a Contused lacerated wound (CLW) on forehead. Cytology revealed Actinomycosis. He subsequently developed upper eyelid actinomycotic inflammatory swelling. Modified Welsh treatment was started and five months of therapy resulted in complete resolution of the infection. Hence any wound with repeated infection should be examined for Actinomycosis. When identified at the right time, such infections show dramatic response to Modified Welsh Therapy.